Enhancement of antifungal activity and transdermal delivery of 5-flucytosine via tailored spanlastic nanovesicles: statistical optimization, in-vitro characterization, and in-vivo biodistribution study - Safhi, Awaji Y.; Naveen, Nimbagal Raghavendra; Rolla, Krishna Jayanth; Bhavani, Penmetsa Durga; Kurakula, Mallesh; Hosny, Khaled M.; Abualsunun, Walaa A.; Alissa, Mohammed; Alsalhi, Abdullah; Alahmadi, Amerh Aiad; Zoghebi, Khalid; Halwaani, Abdulrahman Sindam; et al. (Frontiers in Pharmacology, 2023)
Aim and background: This current study aimed to load 5-flucytosine (5-FCY) into spanlastic nanovesicles (SPLNs) to make the drug more efficient as an antifungal and also to load the 5-FCY into a hydrogel that would allow for enhanced transdermal permeation and improved patient compliance. Methods: The preparation of 5-FCY-SPLNs was optimized by using a central composite design that considered Span 60 (X1) and the edge activator Tween 80 (X2) as process variables in achieving the desired particle size and entrapment efficiency. A formulation containing 295.79 mg of Span 60 and 120.00 mg of Tween 80 was found to meet the prerequisites of the desirability method. The optimized 5-FCY-SPLN formulation was further formulated into a spanlastics gel (SPG) so that the 5-FCY-SPLNs could be delivered topically and characterized in terms of various parameters. Results: As required, the SPG had the desired elasticity, which can be credited to the physical characteristics of SPLNs. An ex-vivo permeation study showed that the greatest amount of 5-FCY penetrated per unit area (Q) (mg/cm2) over time and the average flux (J) (mg/cm2/h) was at the end of 24 h. Drug release studies showed that the drug continued to be released until the end of 24 h and that the pattern was correlated with an ex-vivo permeation and distribution study. The biodistribution study showed that the 99mTc-labeled SFG that permeated the skin had a steadier release pattern, a longer duration of circulation with pulsatile behavior in the blood, and higher levels in the bloodstream than the oral 99mTc-SPNLs. Therefore, a 5-FCY transdermal hydrogel could possibly be a long-acting formula for maintenance treatment that could be given in smaller doses and less often than the oral formula.